2014
DOI: 10.1111/tpj.12501
|View full text |Cite
|
Sign up to set email alerts
|

Decreased capacity for sodium export out of Arabidopsis chloroplasts impairs salt tolerance, photosynthesis and plant performance

Abstract: SUMMARYSalt stress is a widespread phenomenon, limiting plant performance in large areas around the world. Although various types of plant sodium/proton antiporters have been characterized, the physiological function of NHD1 from Arabidopsis thaliana has not been elucidated in detail so far. Here we report that the NHD1-GFP fusion protein localizes to the chloroplast envelope. Heterologous expression of AtNHD1 was sufficient to complement a salt-sensitive Escherichia coli mutant lacking its endogenous sodium/p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(57 citation statements)
references
References 65 publications
(100 reference statements)
2
53
0
Order By: Relevance
“…In this study, the authors also suggested that sodium influx could be balanced by the sodium: proton antiporter NHD1. This transporter, previously identified both in chloroplast and plasma membrane proteomes (15,101), was recently characterized as a sodium exporter of the chloroplast envelope (103). In the AT_CHLORO database, BASS2 was found associated with both envelope and thylakoid membranes, although NDH1 was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the authors also suggested that sodium influx could be balanced by the sodium: proton antiporter NHD1. This transporter, previously identified both in chloroplast and plasma membrane proteomes (15,101), was recently characterized as a sodium exporter of the chloroplast envelope (103). In the AT_CHLORO database, BASS2 was found associated with both envelope and thylakoid membranes, although NDH1 was not detected.…”
Section: Discussionmentioning
confidence: 99%
“…In order to cope with salt stress, plants produce protective compounds, adjust their ion homeostasis, and remodel primary metabolism to serve the energy demand under stress (Deinlein et al, 2014;Müller et al, 2014). Focusing on Arabidopsis roots, which are the primary targets of salt stress, this study revealed a rapid and substantial reprogramming of the transcriptome leading to metabolic adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…In C 3 plants where there is no such role for Na + , accumulation of Na + in the chloroplast may be deleterious. Indeed, using knockout lines of NHD1 in Arabidopsis, (Müller et al, 2014) showed that the inability to export Na + out of the chloroplast can impair the salt tolerance, photosynthesis and growth of the plants. It can be inferred from the NHD1 function in this study that proton pumps should also be crucial for Na + homeostasis in the chloroplast.…”
Section: Exclusion Of Na+ From Chloroplast Is Important For Salt Strementioning
confidence: 99%